Uji Kekerasan Bahan Gear Sprocket Dengan Campuran Timah (Sn) - Muh Anhar; Normansyah Normansyah (Journal of Applied Mechanical Engineering and Renewable Energy, 2021)
The Material Test Process of Gear Sprocket includes the process of cutting the material used as the Material Test sample which is mixed or not mixed. In the sample that is mixed, namely the base metal that has been cut with a value ratio of 10:2 Ounce of Material Gear Sprocket 10 and Tin Material 2 Ounces, fusion will be carried out for the process of blending/unifying the two types of material as sample material. Test the material with the mixing, while the Gear Sprocket material sample that was not mixed was also taken a load value of 10 Ounces, for the test sample where the mixing was not carried out. The test results data from the Gear Sprocket material sample with Tin mixing with four tests from several different surface parts obtained the value 51.5, 55, 50, 53 kgf. While the sample of the Gear Sprocket material without mixing the tin, the results obtained are the values ​​of 50, 51, 50, 50 kgf. In combining the Tin Material with the base metal Gear Sprocket with the ratio of 2 Ounce Tin Material and 10 Ounce Gear Sprocket Material, the hardness results are unstable, so the value obtained from the material being treated is obtained a value that is less likely, while the material test value of the Material Gear Sprockets that are not combined have good results from each surface even though the hardness value is slightly smaller than the result of the material being treated.